Effects of graphite on rheological and conventional properties of bituminous binders - Erkuş, Yunus; Kök, Baha Vural; Yilmaz, Mehmet (Elsevier B.V., 2017)
In this study, the effects of graphite used for developing the rheological and conventional properties of bitumen were investigated using various bituminous binder tests. Penetration, softening point, rotational viscosity (RV), dynamic shear rheometer (DSR) and bending beam rheometer (BBR) tests were applied to bituminous binders modified with four different proportions of graphite by bitumen weight. The penetration values declined while softening point values increased with rising graphite content. While graphite induced 8 °C increases in mixing-compacting temperature by increasing the viscosity values, it also increased the rutting parameter. According to the BBR test, the deformation and stiffness values changed significantly with increasing graphite content, but the m-values did not change significantly. These results showed that graphite generally used for improving the thermal properties can improve to high temperature performance of mixtures. © 2017 Chinese Society of Pavement Engineering
Keywords: Bitumen; Conventional properties; Graphite; Rheological properties